The thinking processes of prospective mathematics teachers in reversibly translating nets into geometric shapes - Sandie Sandie; Syarifah Fadillah; Dewi Risalah; Al-Iman Nuryadin (CV. FOUNDAE, 2026)
Background: Spatial reasoning is a fundamental component of geometry learning, particularly in translating between two-dimensional nets and three-dimensional geometric shapes. For prospective mathematics teachers, the ability to perform such spatial translations is essential because it influences conceptual understanding and future instructional practices. However, correct answers in spatial tasks do not always indicate genuine conceptual understanding. Aims: This study aims to explore and describe the thinking processes of prospective mathematics teachers when translating spatial representations, specifically from nets to geometric shapes and from geometric shapes to nets. The scope focuses on identifying qualitative characteristics of their thinking processes in spatial translation tasks. Methods: This research employed a qualitative approach involving 12 prospective mathematics teachers enrolled in the Mathematics Education Study Program, Faculty of Mathematics, Natural Sciences, and Technology, Universitas PGRI Pontianak. Participants were selected using purposive sampling. Data were collected through spatial translation tasks followed by semi-structured interviews. Interview data were audio-recorded, transcribed verbatim, and analyzed qualitatively to identify patterns in participants’ thinking processes. Result: The findings revealed five distinct characteristics of thinking processes: (1) correct and understanding the concept, (2) correct but not understanding the concept, (3) correct through reflection, (4) wrong but understanding the concept, and (5) wrong and not understanding the concept. The results indicate that answer correctness does not necessarily reflect conceptual understanding, and that reflection plays a crucial role in reconstructing spatial concepts. Conclusion: This study emphasizes the importance of conceptual understanding and reflective thinking in geometry instruction and provides insights for mathematics teacher education programs in designing learning experiences that develop prospective teachers’ spatial reasoning skills.